Language and Audiological Outcomes Among Infants Implanted Before 9 and 12 Months of Age Versus Older Children: A Continuum of Benefit Associated With Cochlear Implantation at Successively Younger Ages. Issue 5 (June 2021) - Chweya, Cynthia M.; May, Matthew M.; DeJong, Melissa D.; Baas, Becky S.; Lohse, Christine M.; Driscoll, Colin L. W.; Carlson, Matthew L.
Abstract : Objective: To compare language and audiological outcomes among infants (<9 and <12 mo) and older children receiving cochlear implantation (CI). Study design: Retrospective chart review. Setting: Tertiary academic referral center. Patients: Pediatric patients receiving CI between October 1995 and October 2019. Intervention: Cochlear implantation Main Outcome Measures: Most recent language and audiological assessment scores were evaluated by age group. Results: A total of 118 children were studied, including 19 who were implanted <9 months of age, 19 implanted 9 to <12 months of age, and 80 implanted 12 to <36 months of age. The mean duration of follow-up was 7.4 ± 5.0 years. Most recent REEL-3 receptive (88 ± 12 vs. 73 ± 15; p  = 0.020) and expressive (95 ± 13 vs. 79 ± 12; p  = 0.013) communication scores were significantly higher in the <9 months group compared to the 9 to <12 months group. PLS and OWLS auditory comprehension and oral expression scores were significantly higher in the <12 months group compared to the 12 to <36 months group. The difference in NU-CHIPS scores between <12 and 12 to <36 months was statistically significant (89% ± 6 vs. 83% ± 12; p  = 0.009). LNT scores differed significantly between <9 and 9 to <12 months (94% ± 4 vs. 86% ± 10; p  = 0.028). Conclusions: The recent FDA expansion of pediatric CI eligibility criteria to include infants as young as 9 months of age should not serve as a strict clinical cutoff. Rather, CI can be pursued in appropriately selected younger infants to optimize language and audiological outcomes. Abstract : Supplemental Digital Content is available in the text